2019
DOI: 10.1111/resp.13519
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the measurement properties of the incremental shuttle walk test in patients with severe asthma

Abstract: Background and objective:We investigated the repeatability and validity of the incremental shuttle walk test (ISWT) distance compared to peak oxygen uptake (VO 2pk ) during maximal incremental cycle ergometer (ICE) and treadmill (ITM) tests in adults with severe asthma. Methods: Adults with severe asthma, Medical Research Council (MRC) dyspnoea ≥2, were recruited from specialists caring for patients with severe asthma. All participants performed three ISWT (familiarization and two subsequent tests on the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Although several studies (Bradley et al, 1999; Vallier et al, 2016; Lanza et al, 2018; Majd et al, 2019) have shown a good association between maximal oxygen consumption (VO 2 peak) measured during CPET and the distance covered in the MST in adults, little is known for pediatric populations. Evidence suggests differences in both exercise capacity parameters and clinical characteristics of asthma between children and adults (Jenkins et al, 2003; Vinet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies (Bradley et al, 1999; Vallier et al, 2016; Lanza et al, 2018; Majd et al, 2019) have shown a good association between maximal oxygen consumption (VO 2 peak) measured during CPET and the distance covered in the MST in adults, little is known for pediatric populations. Evidence suggests differences in both exercise capacity parameters and clinical characteristics of asthma between children and adults (Jenkins et al, 2003; Vinet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with asthma perceived themselves as unfit and were not confident with exercise, but they performed all the IST well, with a learned incremental increase seen between the three tests. The IST also correlated with the calculated and validated, but more complex, cardiopulmonary exercise test‐derived peak oxygen uptake (VO 2Pk ) …”
Section: Developing Biomarkers For Use In Asthmamentioning
confidence: 84%
“…Exercise capacity and activity are frequently reduced in asthma of all severities, especially those with severe disease, yet as mentioned, this is often not measured, with reproducible, accurate but also practical measures required. A team of UK‐based researchers investigated the incremental shuttle walk test (IST), a field test, against the more involved and specialized cardiopulmonary exercise test in adults with severe asthma . Subjects with asthma perceived themselves as unfit and were not confident with exercise, but they performed all the IST well, with a learned incremental increase seen between the three tests.…”
Section: Developing Biomarkers For Use In Asthmamentioning
confidence: 99%
“…We read with interest the study of Majd et al regarding the measurement properties of incremental shuttle walking test (ISWT) in patients with asthma. 1 In this elegant and well-designed study, authors investigated the reproducibility of ISWT and the correlation of ISWT distance with peak oxygen uptake values among patients with asthma. Exercise intolerance and reduced physical activity are common in this patient population, and current literature indicates that exercise training is an efficient adjunctive therapy among asthmatic patients.…”
Section: Incremental Shuttle Walking Test In Patients With Asthmamentioning
confidence: 99%